2021
DOI: 10.1152/jn.00053.2021
|View full text |Cite
|
Sign up to set email alerts
|

Trial-by-trial modulation of express visuomotor responses induced by symbolic or barely detectable cues

Abstract: Human cerebral cortex can produce visuomotor responses that are modulated by contextual and task-specific constraints. However, the distributed cortical network for visuomotor transformations limits the minimal response time of that pathway. Notably, humans can generate express visuomotor responses in arm muscles that are inflexibly tuned to the target location and occur 80-120ms from stimulus presentation (stimulus-locked responses, SLRs). This suggests a subcortical pathway for visuomotor transformations tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 49 publications
8
49
0
Order By: Relevance
“…If similar mechanisms govern express arm responses in our paradigm, then cortical inputs related to implied motion and the timing of target appearance would increase the pre-target activity within the superior colliculus. Express arm responses have been potentiated in other behavioural paradigms that presumably engage different top-down inputs into the superior colliculus (3, 23, 24, 29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If similar mechanisms govern express arm responses in our paradigm, then cortical inputs related to implied motion and the timing of target appearance would increase the pre-target activity within the superior colliculus. Express arm responses have been potentiated in other behavioural paradigms that presumably engage different top-down inputs into the superior colliculus (3, 23, 24, 29).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging target paradigm (23) has emerged as an efficient means to elicit express arm responses, increasing the prevalence and magnitude of the response (5,12,24). Past work has investigated how certainty about the time of target emergence (5), cueing (24), or the properties of the emerging target (5,12) influence the express arm response. All such work using the emerging target task, as well as all past studies of the express arm response (1,4,9) investigated reaches made with one arm.…”
Section: Comparison To Past Studies and Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, previous EMG work shown that humans can produce extremely fast stimulus-driven arm muscles responses that are inflexibly locked in space and time to visual stimuli (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), which were originally termed stimulus-locked responses (SLRs; 5). Specifically, the SLRs consistently encode the location of a visual stimulus within ~100ms from its presentation, irrespective of the mechanical RT.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the neural pathway for SLRs has been hypothesized to parallel that of express saccades (19), which involves the superior colliculus and its downstream projection to the reticular formation (20)(21)(22)(23)(24). Consequently, we and others have referred to short-latency EMG responses observed within the established "SLR" time window as "express" arm muscles responses (16)(17)(18), and will use this terminology here.…”
Section: Introductionmentioning
confidence: 99%